2019
DOI: 10.3906/sag-1907-166
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N-methyltransferase expression and its association with phospho-Akt, p53 expression, and survival in high-grade endometrial cancer

Abstract: Background/aim: Nicotinamide N-methyltransferase (NNMT) is an enzyme that is overexpressed in malignancies. NNMT expression has not been previously studied in endometrial cancer (EC). Increased phospho-Akt (pAkt) levels in response to NNMT overexpression have been reported in in vitro studies of different cancer types. We assayed NNMT expression in primary and metastatic high-grade EC and investigated the relationship of NNMT with p53, pAkt, and survival. Materials and methods: NNMT, pAkt, and p53 expressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…5A and Supplementary Table 3 ). Among them, NNMT was involved in PI3K/AKT signaling pathway and was the most interest target candidate of TTPAL [ 9 , 10 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…5A and Supplementary Table 3 ). Among them, NNMT was involved in PI3K/AKT signaling pathway and was the most interest target candidate of TTPAL [ 9 , 10 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Increasing lines of evidence showed that NNMT is significantly overexpressed in various malignancies 8 , 9 , 11 , 15 , 18 , 19 , 21 , 22 . Interestingly, we showed that NNMT is also highly expressed in CRC, especial in tumor stroma, but is hardly found to be expressed in ANT, which indicated that NNMT is mainly resided in the tumor stroma of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…1-methylnicotinamide (1-MNA), an endogenous metabolite of nicotinamide (NA), is generated by NNMT 7 . Accumulating evidence indicates that NNMT is highly expressed in numerous malignancies, including renal cell cancer 8 , breast cancer 9 , 10 , non-small cell lung cancer 11 , 12 , bladder cancer 13 , cervical cancer 14 , gastric cancer 15 , 16 , ovarian cancer 17 , 18 , esophageal squamous cell carcinoma 19 , hepatocellular carcinoma 20 , 21 and endometrial cancer 22 . In addition, NNMT is found to be positively correlated with unfavorable clinicopathological features based on previous studies, including advanced clinical stage, distant metastasis and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that NNMT is a potential marker in some cancers (Lu and Long, 2018), few studies have focused on the biological role of NNMT. So far, Seta et al found that overexpression of NNMT was associated with upregulation of an anti-apoptotic protein survivin-Ex3 in OSCC cell line (HSC-2) (Seta et al, 2019), and Akar et al reported that NNMT overexpression was correlated with aberrant p53 and phospho-Akt expression in high-grade endometrial cancer (Akar et al, 2019). NNMT was reported to regulate methylation of tumorassociated genes.…”
Section: Discussionmentioning
confidence: 99%